Planting Cypress - Susan W. Vince; Mary L. Duryea (EDIS)
This publication provides guidelines on where, how, and when to plant cypress. It identifies the factors most likely to influence the success of planting and explains how the landowner can plan and implement an effective planting program. Incentives for planting cypress may be available; more information can be obtained from your Division of Forestry county forester or UF-IFAS county extension agent. This document is Circular 1458, one of a series of the School of Forest Resources and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published August 2004.